2008
DOI: 10.1021/jp712106d
|View full text |Cite
|
Sign up to set email alerts
|

In situ Preparation of Gold Nanoparticles of Varying Shape in Molecular Hydrogel of Peptide Amphiphiles

Abstract: We have synthesized the gold nanoparticles (GNPs) of different shaped by in situ reduction within the structuredirecting low molecular weight gel template of tryptophan-containing peptide amphiphiles in water without using any external reducing or capping agents. Gold nanocrystals with sheet, wire, octahedral, and decahedral shapes were modulated with the help of the different morphology of the supramolecular gel network. The gel morphology at minimum gelation concentration is the prime requirement to prepare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 50 publications
0
83
0
Order By: Relevance
“…11 The in situ formation of metallic nanoparticles into a hydrogel without an external reducing agent notably increases its potential applications. 12 These metal nanoparticles-hydrogel nanocomposite materials can be used for various applications such as catalysis, sensors, drug delivery, biological labeling as well as antimicrobial agents. Several studies have been performed on the formation of metal nanoparticle-hydrogel composites through in situ reduction of the metal ions by the gelator molecule.…”
Section: Resultsmentioning
confidence: 99%
“…11 The in situ formation of metallic nanoparticles into a hydrogel without an external reducing agent notably increases its potential applications. 12 These metal nanoparticles-hydrogel nanocomposite materials can be used for various applications such as catalysis, sensors, drug delivery, biological labeling as well as antimicrobial agents. Several studies have been performed on the formation of metal nanoparticle-hydrogel composites through in situ reduction of the metal ions by the gelator molecule.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that proteins can bind AgNPs through free amine groups and provide a good protecting environment for metal hydrosols during the growth processes. [26,27] Figure 4 shows some pronounced absorbance bands at around 3400-3450/cm (N-H stretching), and 1620-1650/cm (aromatic rings), suggest the presence of proteins on the surface of Ag-core particles. The peak around 3400-3450/cm of plant proteins in the nanoparticles shell is much narrower.…”
Section: Resultsmentioning
confidence: 99%
“…179,180 By combining lithography with structuredirecting PAs, one can begin to control the nanoparticle 80 morphology of a wide variety of materials, including metals like gold. 181 This latter example, controlling the growth of gold nanoparticles, actually uses a subtly different class of PA as the structure-directing scaffold. The PA consists of only two major components; the aliphatic tail and a positively 85 charged amino acid or dipeptide head group.…”
Section: Peptide-amphiphilesmentioning
confidence: 99%